2013
DOI: 10.1371/journal.pone.0075916
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intracellular Localization of SOD1 in Leukocytes from Patients with Sporadic Amyotrophic Lateral Sclerosis

Abstract: Several lines of evidence support the hypothesis of a toxic role played by wild type SOD1 (WT-SOD1) in the pathogenesis of sporadic amyotrophic lateral sclerosis (SALS). In this study we investigated both distribution and expression profile of WT-SOD1 in leukocytes from 19 SALS patients and 17 healthy individuals. Immunofluorescence experiments by confocal microscopy showed that SOD1 accumulates in the nuclear compartment in a group of SALS subjects. These results were also confirmed by western blot carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…This view has been challenged by studies reporting misfolded SOD1 accumulation in motor neurons [6, 19, 22, 53] and glia [18] of spinal cords as well as in PBMCs [11] and lymphocytes [27] from SALS patients. Neural precursor cell (NPC)- [29] or patient- [57] derived astrocytes, as well as NPC-derived oligodendrocyte progenitors [17] from both SOD1 mutant or sporadic ALS patients have been reported to be toxic to co-cultured normal motor neurons.…”
Section: Introductionmentioning
confidence: 99%
“…This view has been challenged by studies reporting misfolded SOD1 accumulation in motor neurons [6, 19, 22, 53] and glia [18] of spinal cords as well as in PBMCs [11] and lymphocytes [27] from SALS patients. Neural precursor cell (NPC)- [29] or patient- [57] derived astrocytes, as well as NPC-derived oligodendrocyte progenitors [17] from both SOD1 mutant or sporadic ALS patients have been reported to be toxic to co-cultured normal motor neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, the SOD1 distribution allowed to distinguish two different categories of patients: the first group had perinuclear SOD1 aggregates and the second one higher nuclear SOD1. In addition, Cereda [26] observed that patients with more perinuclear SOD1 expressed a major amount of insoluble proteins while the other group, characterized by predominant nuclear SOD1, had especially soluble fractions. Eventually, the authors tested whether these findings had clinical correlates (see Table 1 for general characteristics of patient cohort).…”
Section: Sod1 Aggregationmentioning
confidence: 98%
“…Given that, the hypothesis was that wild-type SOD1, under many environmental triggers, became misfolded SOD1 with reduced antioxidant activity (loss of function) and acquired toxic property as mutant SOD1 has [25]. Cereda and co-workers [26] demonstrated a bigger total amount of SOD1 in PBMCs of SALS patients than in cells of healthy controls or Alzheimer patients [26]. Curiously, the SOD1 distribution allowed to distinguish two different categories of patients: the first group had perinuclear SOD1 aggregates and the second one higher nuclear SOD1.…”
Section: Sod1 Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PBMCs share more than 80% of their transcriptomes with other tissues, including the central nervous system, and can be isolated easily from patients by venipuncture [26]. Previous studies demonstrated that PBMCs are a valid cell model to study ALS [26][27][28][29]. Based on this and on the new vision of ALS as a pathology affecting not only motor neurons exclusively but also other cell systems [30][31][32], we investigated the possible role of VAPB as a pathologic marker in PBMCs from patients with sALS.…”
Section: Introductionmentioning
confidence: 99%